2016
DOI: 10.3748/wjg.v22.i40.8929
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota in pouchitis and ulcerative colitis

Abstract: AIMTo investigate the changes in microbiota in feces of patients with ulcerative colitis (UC) and pouchitis using genomic technology.METHODSFecal samples were obtained from UC patients with or without an ileal pouch-anal anastomosis (IPAA) procedure, as well as healthy controls. The touchdown polymerase chain reaction technique was used to amplify the whole V3 region of the 16S rRNA gene, which was transcribed from DNA extracted from fecal samples. Denaturing gradient gel electrophoresis was used to separate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 35 publications
3
29
0
1
Order By: Relevance
“…Similar to IBD, bacterial diversity has been shown to be reduced in patients with pouchitis with changes in both anaerobic and aerobic bacteria noted . Analysis of faecal samples has shown higher levels of aerobes and lower levels of anaerobes in patients with pouchitis when compared with controls without pouchitis (Table ) (both UC and FAP) …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar to IBD, bacterial diversity has been shown to be reduced in patients with pouchitis with changes in both anaerobic and aerobic bacteria noted . Analysis of faecal samples has shown higher levels of aerobes and lower levels of anaerobes in patients with pouchitis when compared with controls without pouchitis (Table ) (both UC and FAP) …”
Section: Resultsmentioning
confidence: 96%
“…Both ciprofloxacin and metronidazole are the first line treatments for pouchitis and result in clinical remission in about 60% of patients . As both C. perfringens and E. coli have been associated with pouchitis, this gives further credence to the concept that manipulating the gut microbiota to alter specific bacteria may help prevent this disease.…”
Section: Resultsmentioning
confidence: 99%
“…The colonic epithelium is a single layer of cells undergoing continuous renewal which is able to respond to a wide range of stimuli, to absorb and to secrete. The etiology of pouchitis and IBD is still debated, but many evidences point to a disturbance between gut wall and commensal bacteria in certain individuals that are genetically susceptible (Li et al, ; Wu & Shen, ). Since VSL#3 is recommended by (American Gastroenterological Association) and ECCO (European Crohńs and Colitis Organization) guidelines for the prevention and remission induction or maintenance of pouchitis (Mowat et al, ), it would have been of some interest to look at the relationships between the bacteria present in the probiotic mix and the epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors like nutrients, polyamines, short chain fatty acids, lipids, and trace elements present in the gut may affect positively or negatively the intestinal wound healing. Indeed, for example, progression and flares of Inflammatory Bowel Diseases (IBD) may result also from the presence of microbes and microbe‐derived substances in the gut, even after the inciting agents responsible for the initiation of inflammation are controlled (Li et al, ; Wu & Shen, ). Recently, it has been reported that the secretion of alpha‐hemolysin by Escherichia coli disrupts tight junctions in ulcerative colitis patients (Mirsepasi‐Lauridsen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in the intestinal microbiota have also been reported in ulcerative colitis, although to a lesser degree compared to CD. Less diverse microbiota profiles have been demonstrated in ulcerative colitis patient samples, and in particular, the finding of increased Clostridium perfringens in faeces suggests a role in disease exacerbation . A decrease in Fusicatenibacter saccharivorans in patients with active ulcerative colitis has also been reported, in contrast to the increase observed in patients with quiescent disease …”
Section: Mucosal Vs Faecal Microbial Populationsmentioning
confidence: 98%